2009
DOI: 10.1037/a0016081
|View full text |Cite
|
Sign up to set email alerts
|

Preventing vicarious traumatization of mental health therapists: Identifying protective practices.

Abstract: This qualitative study identified protective practices that mitigate risks of vicarious traumatization (VT) among mental health therapists. The sample included six peer-nominated master therapists, who responded to the question, "How do you manage to sustain your personal and professional well-being, given the challenges of your work with seriously traumatized clients?" Data analysis was based upon Lieblich, Tuval-Mashiach, and Zilber's (1998) typology of narrative analysis. Findings included nine major themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
212
1
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(237 citation statements)
references
References 30 publications
12
212
1
12
Order By: Relevance
“…Secondary Traumatic Stress was negatively correlated with supervisory support (p=.002), but after effect size was calculated the strength of association was not as strong as organizational support and trauma-informed caregiver development.This does not negate the importance of supervisory support as this study found supervisory support to be significantly associated with higher levels of compassion satisfaction (p < .001) and the strength of this relationship was medium when effect sizes were calculated. Countless other researchers have found lack ofsupervisory support to be a strong predictor of burnout and secondary traumatic stress (Harrison & Westwood, 2009;Jankoski, 2010;Tehrani, Osborne, & Lane, 2012) and correlated with trauma caregiver perceptions of client care (Räikkönen, Perälä, &Kahanpää, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary Traumatic Stress was negatively correlated with supervisory support (p=.002), but after effect size was calculated the strength of association was not as strong as organizational support and trauma-informed caregiver development.This does not negate the importance of supervisory support as this study found supervisory support to be significantly associated with higher levels of compassion satisfaction (p < .001) and the strength of this relationship was medium when effect sizes were calculated. Countless other researchers have found lack ofsupervisory support to be a strong predictor of burnout and secondary traumatic stress (Harrison & Westwood, 2009;Jankoski, 2010;Tehrani, Osborne, & Lane, 2012) and correlated with trauma caregiver perceptions of client care (Räikkönen, Perälä, &Kahanpää, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has strong practical implications and is supported by the trauma literature. Many trauma experts believe that trauma caregivers are at higher risk for secondary traumatic stress if their entire caseload consists of individuals or animals whohave experienced trauma (Bell, Kulkarni, & Dalton, 2003;Harrison & Westwood, 2009;Pearlman & McKay, 2008;Saakvitne& Pearlman, 1996). This finding supports the ideathat trauma caregivers continuously providing services to survivors of trauma are at higher risk of developing secondary traumatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Harrison and Westwood (2009) attempted to identify protective practices that reduce risks of vicarious traumatization among mental health therapists. Possible participants were asked to fill out the Professional Quality of Life: Compassion Fatigue and Satisfaction Subscales, R-III (Pro-QOL), which is a brief quantitative scale used for screening purposes only.…”
Section: Compassion Satisfaction and Fatigue Subscales Of The Professmentioning
confidence: 99%
“…Tout d'abord, fournir de l'information aux nouveaux employés des impacts potentiels du travail avec une clientèle souffrante ou victime de traumatisme les protège déjà contre la FC et le TV (Chrestman, 1995;Dane, 2002; Neuman & Gamble, 1995;Newell & MacNeil, 2010;Richardson, 2001 (Bell et al, 2003;Bourassa, 2009;Brady et al, 1999;Catherall, 1995a;Clemans, 2005;Collins & Long, 2003b;Cunningham, 2003Cunningham, , 2004Dane, 2002;Gentry, 2002;Harr & Moore, 2011;Hesse, 2002;Killian, 2008; Pearlman, 1999;Perreault, 2004;Richardson, 2001;sommer, 2008;Sprang et al, 2007;Trippany et al, 2004). D'ailleurs, l'autosensibilisation consciente constitue aussi un facteur protégeant les intervenants de la FC et du TV (Figley, 2002b;Harrison & Westwood, 2009;Hayes, 2004;Perreault, 2004;Stamm et al, 2002;Trippany et al, 2004). Il s'agit pour …”
Section: La Formationunclassified